Corien W. Wiersma, Dimitris Agnousiotis, Evangelia Karimali, Wietske Prummel and H. Reinder Reinders. Magoúla Pavlína. A Middle Bronze Age site in the Soúrpi Plain. pp. 189, 43 col. ills incl. maps + 58 b&w and 1 mixed, 4 tables. 2016. Groningen: Barkhuis - Dickinson , Oliver (Journal of Greek Archaeology, 2020)
Magoula Pavlina is a slight elevation, about 1.9 m high and 4 hectares in area, less than 1 km from the beach ridge of an inlet from the Pagasitic Gulf and close to the Salambrias river that runs into the inlet, in a well-watered area of eastern Thessaly that used to be marshy but was drained for agriculture in the 1930s. It is not actually clear that it is a magoula, that is, an artificial mound built up from the remains of ancient settlement debris (p. 18, bottom), like several important sites in the neighbourhood such as Zerelia (Wace and Thompson 1912, 150–66); but some prehistoric pottery was noticed on its surface in 1978. Ploughing for the first time (in the modern era, at least) in 1996 brought a mass of artefacts to the surface, and the Groningen Institute of Archaeology, which was conducting a survey in the region in partnership with the Ephorate of Prehistoric and Classical Antiquities in Volos, quickly made an arrangement with the land-owner to give the site a survey. In two days over 9000 items were collected, predominantly pieces of pottery; a sample consisting of pottery, stone and clay artefacts, and mammal and mollusc remains was reserved for close study. This volume publishes the results, replacing earlier partial reports.